Kajian Alih Fungsi Lahan Pertanian Menjadi Sektor Pariwisata di Nagari Tarantang Kecamatan Harau Kabupaten Lima Puluh Kota - Yusyaf, Dhiva Julian; Wilis, Ratna (Al-DYAS, 2024)
This research aims to determine changes in the conversion of agricultural land into the tourism sector in Nagari Tarantang, Harau District, Limapuluh Kota Regency. This type of research is quantitative descriptive. The subjects in this research were agricultural land owners who converted to tourism in Nagari Tarantang, Harau District, Limapuluh Kota Regency. Data collection techniques in this research were observation, questionnaires and documentation. The sampling technique used a total sampling of 10 agricultural land owners who had converted to tourism in Nagari Tarantang, Harau District, Limapuluh Kota Regency. The results of this research conclude: 1) Agricultural land that was converted into tourism land covering an area of 16.7 Ha, the change in land was caused by several factors, namely economic, cultural, political, environmental and new job opportunities.